Pernikahan tanpa Pencatatan: Kegagalan Negara dalam Melindungi Hak Sipil Perempuan dan Anak - Syawal Ridwan (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2025)
This policy article examines the phenomenon of unregistered marriages in Indonesia as a reflection of the state's failure to safeguard the civil rights of women and children. Marriages conducted without official registration—such as religious or customary marriages—pose serious consequences for legal protection, particularly for vulnerable groups. Women are deprived of rights to alimony, protection in divorce, and legal recognition, while children risk being denied birth certificates, limiting their access to education, healthcare, and social assistance. This issue is exacerbated by unequal access to civil registration services in remote areas, low legal literacy, and the dominance of religious and customary norms that often override national law. This paper uses approach using qualitative methods based a descriptive-analytical on literature review, analyzing statutory regulations, institutional reports, and academic publications. Content analysis and the USG framework (Urgency, Seriousness, Growth) are applied to assess the magnitude and developmental risks of the issue. The analysis is grounded in Gramsci’s Hegemony Theory, Legal Pluralism, and Structural Inequality Theory, which reveal a legal gap between formal norms and social practices that leave women and children legally and socially vulnerable. The findings indicate that regulatory reform of marriage registration emerges as the most strategic and effective policy option. In conclusion, the state must take an active role by reforming legal frameworks, expanding access to registration services, integrating local norms, and promoting legal education to ensure equal and just protection for all citizens.